Increased telomerase activity and hTERT expression in human salivary gland carcinomas - Shigeishi, Hideo (D.A. Spandidos, 2011)
Approximately 85% of human malignant tumors express increased levels of telomerase. The marked association of telomerase activity with malignant tissue provides strong evidence that telomerase activity is a significant marker for the diagnosis of cancer. In this study, telomerase activity was examined in 12 benign salivary gland tumors (8 pleomorphic adenomas and 4 adenolymphomas), 24 malignant tumors (15 mucoepidermoid carcinomas, 6 adenoid cystic carcinomas and 3 acinic cell carcinomas) and 6 non-neoplastic salivary glands. The mRNA expression of the human telomerase reverse transcriptase (hTERT) and additional telomerase‑associated proteins (hTEP1, p23, Hsp90 and dyskerin) was also examined. Of the 24 malignant tumors, 15 revealed strong telomerase activity. The non-neoplastic salivary glands appeared to have a negative telomerase expression. Furthermore, telomerase activity was significantly higher in high-grade mucoepidermoid carcinomas compared to low‑grade ones (Student's t-test, p<0.05). A significant correlation was found between telomerase activity and mRNA expression of hTERT in 15 cases, including non-neoplastic salivary glands and tumors (Spearman's rank correlation test, p<0.05). Furthermore, a significant correlation was found between telomerase activity and mRNA expression of EGFR (Spearman's rank correlation test, p<0.001). The results suggest that not only hTERT, but also EGFR play a significant role in the activation of telomerase. In conclusion, the results suggest that telomerase activity and hTERT/EGFR mRNA expression are useful markers for the detection of malignant cells in salivary gland carcinomas. Moreover, our results indicated that telomerase activity determines the degree of malignancy of mucoepidermoid carcinoma.